2017
DOI: 10.1371/journal.pone.0181135
|View full text |Cite
|
Sign up to set email alerts
|

The association between ethnicity and vaginal microbiota composition in Amsterdam, the Netherlands

Abstract: ObjectiveTo evaluate whether ethnicity is independently associated with vaginal microbiota (VMB) composition in women living in Amsterdam, the Netherlands, as has been shown for American women.MethodsWomen (18–34 years, non-pregnant, N = 610) representing the six largest ethnic groups (Dutch, African Surinamese, South-Asian Surinamese, Turkish, Moroccan, and Ghanaian) were sampled from the population-based HELIUS study. Sampling was performed irrespective of health status or healthcare seeking behavior. DNA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
137
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(166 citation statements)
references
References 40 publications
(69 reference statements)
14
137
2
3
Order By: Relevance
“…Here, African communities were dominated by L. iners and by a variable mixture of facultative anaerobic bacteria [24,68,81]. Similarly, in a Dutch study about the composition of vaginal microbiome it was significantly associated with ethnic groups where women from African descents had the main occurrence of clusters determined by Gardnerella vaginalis or dysbiosis [82].…”
Section: Ethnicitymentioning
confidence: 77%
“…Here, African communities were dominated by L. iners and by a variable mixture of facultative anaerobic bacteria [24,68,81]. Similarly, in a Dutch study about the composition of vaginal microbiome it was significantly associated with ethnic groups where women from African descents had the main occurrence of clusters determined by Gardnerella vaginalis or dysbiosis [82].…”
Section: Ethnicitymentioning
confidence: 77%
“…Sampling was stratified by ethnic group and included the six largest ethnic groups in the city (Dutch, African Surinamese, South-Asian Surinamese, Turkish, Moroccan, and Ghanaian). In a subsample, a cross-sectional study on the association of ethnicity with VMB composition was performed (Borgdorff et al, 2017). For this sub-study, vaginal samples of 546 pre-menopausal women were sequenced.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Second, each ASV/OTU was assigned to one of four "bacterial groups" based on the published literature (Supplementary Material 1) as follows: (1) lactobacilli; (2) BVanaerobes; (3) pathobionts; and (4) a rest group called "other bacteria" (which contained mostly skin and Bifidobacteria). Pathobionts were defined as all bacterial taxa that have been reported in the literature as having been associated with invasive disease, and are not typically associated with BV; we also included STI pathogens in this category because their mean relative abundances were too low to justify a separate bacterial (Borgdorff et al, 2017;van de Wijgert et al, 2020a,b). b Non-minority is defined as at least 1% in at least one sample.…”
Section: Sequencing Data Processingmentioning
confidence: 99%
“…Increasing evidence has shown that the bacteria within this community, referred to here as the vaginal microbiota (VM), play an important role in protecting the vaginal tract from pathogenic infection, which can have far reaching effects on a woman’s sexual and reproductive health [1, 2]. Several VM compositions have been described, including VM dominated by: 1) Lactobacillus iners; 2) L. crispatus; 3) L. gasseri ; 4) L. jensenii and; 5) VM that are not dominated by a single bacterial species but rather consist of diverse anaerobic bacteria, including Gardnerella vaginalis and members of Lachnospiraceae and Leptotrichiaceaeprevotella [3-5]. Particularly VM that are dominated by L. crispatus are associated with vaginal health, whereas a VM consisting of diverse anaerobes – commonly referred to as vaginal dysbiosis - have been shown to increase a woman’s odds for developing bacterial vaginosis (BV), acquiring STI’s, including HIV, and having an adverse pregnancy outcome [1, 2, 4, 6].…”
Section: Introductionmentioning
confidence: 99%